Konsumsi Junk Food dan Perilaku Picky Eating dengan Status Gizi Anak Sekolah - Ronasari Mahaji Putri; Hilda Mazarina Devi (Jurnal Akademika Baiturrahim Jambi, 2022)
Excessive nutritional status of school children is associated with high consumption of junk food and high Picky eating behavior, which has an unfavorable impact on health. The purpose of the study was to determine the relationship between junk food consumption, Picky eating behavior and the nutritional status of school children. Correlational descriptive research design. The population is 41 children in grade 4 at SDN 1 Landungsari Malang, with a total population technique. The instrument uses a questionnaire of self-identity, Picky eating behavior and consumption of junk food. Data analysis using fisher exact. The results showed that most of the respondents had normal nutritional status, namely 53.6%; most of the respondents have quite Picky eating behavior, namely 73.2%; Most of the respondents have a low consumption of junk food, namely 73.2%. The statistical test revealed that there was no relationship between junk food consumption and nutritional status (p-value 0.753); and there is no relationship between Picky eating and the nutritional status of school children at SDN 1 Landungsari Malang. It is recommended to examine the determinants of junk food consumption and Picky eating behavior in school children